Differential Expression of miRNAs in Hypoxia (“HypoxamiRs”) in Three Canine High-Grade Glioma Cell Lines - Koehler, Jennifer; Sandey, Maninder; Prasad, Nripesh; Levy, Shawn A.; Wang, Xiaozhu; Wang, Xu (Frontiers in Veterinary Science, 2020)
Dogs with spontaneous high-grade gliomas increasingly are being proposed as useful large animal pre-clinical models for the human disease. Hypoxia is a critical microenvironmental condition that is common in both canine and human high-grade gliomas and drives increased angiogenesis, chemo- and radioresistance, and acquisition of a stem-like phenotype. Some of this effect is mediated by the hypoxia-induced expression of microRNAs, small ( 22 nucleotides long), non-coding RNAs that can modulate gene expression through interference with mRNA translation. Using an in vitro model with three canine high-grade glioma cell lines (J3T, SDT3G, and G06A) exposed to 72 h of 1.5% oxygen vs. standard 20% oxygen, we examined the global “hypoxamiR” profile using small RNA-Seq and performed pathway analysis for targeted genes using both Panther and NetworkAnalyst. Important pathways include many that are well-established as being important in glioma biology, general cancer biology, hypoxia, angiogenesis, immunology, and stem-ness, among others. This work provides the first examination of the effect of hypoxia on miRNA expression in the context of canine glioma, and highlights important similarities with the human disease.